Prof. Larry Benowitz: the future of optic nerve regeneration and the difficulty of keeping retinal ganglion cells alive - Fan, Wei-En (Annals of Eye Science, 2018)
Guangzhou Glaucoma Forum (GZGF) was successfully held in the Zhongshan Ophthalmology Center on April 21–22, 2018. The forum gathered domestic and international experts from all over the world, including Prof. Larry Benowitz from Harvard Medical School, Prof. Leopold Schmetterer from Singapore Eye Research Institute, Prof. Anuj Chauhan from University of Florida, Prof. Shlomo Melamed from Israel, and Prof. Keith Barton from Moorfields Eye Hospital. AME editorial team had the honor to interview Prof. Benowitz.